Influence of the tobacco smoking on the bronchial asthma in teenagers - B. Ts. Batozhargalova; Yu. L. Mizernitskiy (Бюллетень сибирской медицины, 2012)
Comparative epidemiological research on studying prevalence tobacco smoking and respiratory symptoms among rural teenagers with bronchial asthma. Control group have made non-smoking (n = 59), and skilled — smoking teenagers (n = 72). Prevalence of smoking among adolescents with bronchial asthma has made 55% against 44,3% on the average at adolescents (p < 0.05). At smokers sick of a bronchial asthma the presence of respiratory complaints, level of СO in exhaled air and urinary cotinine has been raised. Authentic communication of smoking with a series of symptoms bronchial asthma and chronic bronchitis in teenagers, shown is taped by a high and average parity of chances.